SISTEM OUTSOURCING DI SUMATERA BARAT PERSPEKTIF HUKUM ISLAM DAN ETIKA BISNIS ISLAM - hamdanil (Islamic Circle, 2021)
The job vacancies reception in practice with Outsourcing system is seen often not in accordance with the provisions of existing regulations and detrimental to the workers / laborers. Due to the position of workers / laborers tends to be weaker than capital owners. The purpose of this study is to find out the form of employment contracts in Outsourcing system when it is associated with Islamic jurisprudence then to find out the recruitment of employment pattern in Outsourcing system. After that to find out the usage of employment pattern in Outsourcing system and to find out the welfare of employment pattern in Outsourcing system then to reveal the positive and negative impact of job vacancies reception through Outsourcing corporation among capital owners and workers / laborers. For this study, researchers used qualitative method by field research as type. Data Collection Technique that used is interview and documentation. Data was analyzed by descriptive analysis then elaborated. After that data was classified to specific problem aspect and spoken by effective statement. The result of this study is Outsourcing workers / laborers in PT. Andalan Mitra Prestasi Sumatera Barat were matched according Islamic jurisprudence. PT. Andalan Mitra Prestasi Sumatera Barat had instrument that fulfillment the requirement over Islamic contract jurisprudence. Meanwhile according to Islamic business ethic, PT. Andalan Mitra Prestasi Sumatera Barat didn’t run yet the whole of value and basic principle Islamic business ethic.